Chapter 5 The Bridges Over the Miljacka The Long Farewell to Yugoslav Citizenship - Štiks, Igor (Bloomsbury Academic, 2015)
or 'conglomerate' - all occurring in Yugoslavia from mid-1960s at a sometimes vertiginous pace - seem to be interactive parts of the same puzzle. Nevertheless, immediately after the war it appeared that resurrected Yugoslavia and strong patriotism of the national-liberation struggle had given a new impetus to Yugoslavism - this time in a federalist form meant to dissociate the idea from the bitter experiences of pre-war unitarism. Although Yugoslavism itself went through curious re-definitions and had to compete with communist internationalism between 1945 and 1948, socialist nation-building Yugoslavism would be seen and promoted throughout the 1950s as something of uncontested worth. Having described earlier the birth and evolution of Yugoslavism between the mid-nineteenth century and the Second World War, we should recount here its last chapters.